Power Flow Analysis in N-1 Contingency Conditions Due to the Entry of Renewable Power Plants in the Sulselrabar System - Djalal, Muhammad Ruswandi; Saini, Makmur; Yunus, A.M Shiddiq (Politeknik Negeri Ujung Pandang, 2022)
Contingency analysis on a 150 kV network aims to see the network's reliability against interference. Contingency is a scheme for releasing one element of the generating unit or transmission line (N-1), which will affect the performance and reliability of the electric power system. Power flow analysis in an electric power system is an analysis that reveals the performance of an electric power system and the flow for certain conditions when the system is working. The analysis was carried out using the ETAP 16.00 software. The method used was the newton raphson to calculate the load flow in the N-1 contingency condition. From the results of the study, it can be seen that the power flow occurs in each channel of the 150 kV system in the South Sulawesi system. When conducting a contingency analysis of N-1 by removing the load on the middle lane of South Sulawesi, namely Maros and Sidrap, a voltage change occurs, increasing buses experiencing critical and marginal voltage conditions. This happens because of the sudden release of essential loads, so over or under voltage appears on the bus.